2020
DOI: 10.1186/s13071-020-3951-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Simparica Trio™, a novel chewable tablet containing sarolaner, moxidectin and pyrantel, against induced hookworm infections in dogs

Abstract: Background: Ancylostomatids ('hookworms') are among the most important zoonotic nematode parasites infecting dogs worldwide. Ancylostoma caninum and Uncinaria stenocephala are two of the most common hookworm species that infect dogs. Both immature and adult stages of hookworms are voracious blood feeders and can cause death in young dogs before infection can be detected by routine fecal examination. Hence, treatment of both immature and adult stages of hookworms will decrease the risk of important clinical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Simparica Trio ™ also demonstrated ≥ 98.3% efficacy against T. leonina, A. caninum and U. stenocephala in the European study, and 98.6% efficacy against A. caninum in the USA study. These results are in line with the efficacy of Simparica Trio ™ demonstrated against induced hookworm and roundworm infections in dogs [5,6]; thus, the present studies confirm that Simparica Trio ™ is also effective under field conditions in dogs of a variety of breeds, ages, and weight ranges, and in dogs most likely infected with varying numbers of ascarids and hookworms at differing developmental stages at the time of treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Simparica Trio ™ also demonstrated ≥ 98.3% efficacy against T. leonina, A. caninum and U. stenocephala in the European study, and 98.6% efficacy against A. caninum in the USA study. These results are in line with the efficacy of Simparica Trio ™ demonstrated against induced hookworm and roundworm infections in dogs [5,6]; thus, the present studies confirm that Simparica Trio ™ is also effective under field conditions in dogs of a variety of breeds, ages, and weight ranges, and in dogs most likely infected with varying numbers of ascarids and hookworms at differing developmental stages at the time of treatment.…”
Section: Discussionsupporting
confidence: 89%
“…A variety of approved medications are currently available for use in dogs [3,4]. A novel chewable oral tablet (Simparica Trio ™ , Zoetis, Parsippany, NJ, USA) containing sarolaner, moxidectin and pyrantel was recently shown in laboratory studies to be ≥ 95.2% effective against immature adult (L5) and adult T. canis, and ≥ 98.4% effective against L4 larval, immature adult (L5), and adult A. caninum in dogs with experimental infections [5,6]. Here we present two studies in which the safety and efficacy of Simparica Trio ™ was evaluated against naturally occurring gastrointestinal nematode infections in dogs presented as veterinary patients in Europe and the USA.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent efficacy against fleas and ticks observed in these studies, combined with efficacy for the prevention of heartworm and lungworm disease [29,30], and the treatment of roundworm and hookworm infections [31,32] in a single palatable tablet should make Simparica Trio ™ a convenient option for veterinarians and pet owners to routinely treat and control many of the common external and internal parasites of dogs.…”
Section: Discussionmentioning
confidence: 98%
“…This field study confirmed the safety and effectiveness of monthly dosing with Simparica Trio ™ for the treatment and prevention of fleas on dogs under normal home use conditions. This excellent flea control plus the added benefits of the combination providing coverage of the other major ecto-and endoparasites of dogs (ticks, heartworm, lungworm, gastrointestinal nematodes) in a single, palatable monthly dosage make this a convenient treatment option for veterinarians and dog owners [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%